Urochloa grasses swap nitrogen source when grown in association with legumes in tropical pastures - Villegas, Daniel Mauricio; Velásquez, Jaime E.; Arango, Jacobo; Obregon, Karen; Rao, Idupulapati M.; Rosas, Gelber; Oberson, Astrid (MDPI, 2020)
The degradation of tropical pastures sown with introduced grasses (e.g., Urochloa spp.) has dramatic environmental and economic consequences in Latin America. Nitrogen (N) limitation to plant growth contributes to pasture degradation. The introduction of legumes in association with grasses has been proposed as a strategy to improve N supply via symbiotic N2 fixation, but the fixed N input and N benefits for associated grasses have hardly been determined in farmers’ pastures. We have carried out on-farm research in ten paired plots of grass-alone (GA) vs. grass-legume (GL) pastures. Measurements included soil properties, pasture productivity, and sources of plant N uptake using 15N isotope natural abundance methods. The integration of legumes increased pasture biomass production by about 74%, while N uptake was improved by two-fold. The legumes derived about 80% of their N via symbiotic N2 fixation. The isotopic signature of N of grasses in GA vs. GL pastures suggested that sources of grass N are affected by sward composition. Low values of δ 15N found in some grasses in GA pastures indicate that they depend, to some extent, on N from non-symbiotic N2 fixation, while δ 15N signatures of grasses in GL pastures pointed to N transfer to grass from the associated legume. The role of different soil–plant processes such as biological nitrification inhibition (BNI), non-symbiotic N2 fixation by GA pastures and legume–N transfer to grasses in GL pastures need to be further studied to provide a more comprehensive understanding of N sources supporting the growth of grasses in tropical pastures.